Answer:
D ( f x g )(-3) = -304.
Step-by-step explanation:
Given :If f(x) = 5x - 1 and g(x) = 2x² + 1.
To find: what is the value of ( f x g )(-3) .
Solution: We have given that If f(x) = 5x - 1 and g(x) = 2x² + 1.
We need to find ( f x g )(-3) .
f(x) * g(x) = (5x - 1 )* (2x² + 1).
f(x) * g(x) = 10x³+5x -2x² -1 .
f(x) * g(x) = 10x³-2x² + 5x -1.
( f x g )(-3) = 10 (-3)³ - 2(-3)² +5 (-3) -1.
( f x g )(-3) = 10 ( -27) - 2( 9) - 15 -1
( f x g )(-3) = -270 -18 - 16
( f x g )(-3) = -304.
Therefore, D ( f x g )(-3) = -304.